TESTING THE LONG RUN RELATIONSHIP BETWEEN NATURAL GAS UTILIZATION AND ECONOMIC ACTIVITIES IN NIGERIA - Yahya, Binta; Nkwatoh, Louis Sevitienyi (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2021)
This study investigated the long run relationship between natural gas utilization and economic activities in Nigeria using quarterly data from 2001 – 2017. The result showed that there are two cointegration equations implying that there exists a long run relationship between Natural Gas and its determinants. The finding suggests that investing in gas supply infrastructure will enhance gas utilization via power generation, LNG production and Gas-based industrial utilization and also reduce gas flaring while encouraging national growth. A policy implication with respect to this finding is that, stimulating power generation through gas, which constitutes about 60% of power generation mix in Nigeria will help in addressing a lot of our macroeconomic problems like poverty and unemployment because it will stimulate the manufacturing sector and also improve the service sector with much needed electricity supply. As a recommendation, the Federal government should encourage investment both local and foreign in the gas industry so as to harness the abundant gas reserves available in the country and also improve on exploration activities to increase available reserves.